2016
DOI: 10.1515/johr-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Precipitation Conditions on the Growth and Development Dynamics of Five Cultivars of Processing Tomato

Abstract: Cultivation of field tomato in Poland meets unfavorable temperature and precipitation conditions, which affect yield and quality. The aim of the study is to evaluate the effect of temperature and precipitation conditions on the growth and development dynamics of five cultivars of processing tomato. The analysis took into account the key morphological characteristics of the plant, the inflorescence and fruit, which determine the suitability of the cultivar for processing. Analysis of the effect of meteorologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Both diameters were higher in 2015 than in the 2014 tomato growing season. According to Jędrszczyk et al [27] field-grown tomatoes are particularly sensitive to low temperatures, and air temperature can affect the size of marketable tomato fruits. In our study, air temperatures were consistently higher in 2015 than in 2014 (Table 1), this could have had a beneficial effect on fruit length and width.…”
Section: Discussionmentioning
confidence: 99%
“…Both diameters were higher in 2015 than in the 2014 tomato growing season. According to Jędrszczyk et al [27] field-grown tomatoes are particularly sensitive to low temperatures, and air temperature can affect the size of marketable tomato fruits. In our study, air temperatures were consistently higher in 2015 than in 2014 (Table 1), this could have had a beneficial effect on fruit length and width.…”
Section: Discussionmentioning
confidence: 99%
“…The collected data are summarized in Table 1. Jędrszczyk et al [18] and Greco et al [19] mentioned the rainfall item as one of the exogenous variables, but since this study does not consider a model that predicts the yield of tomatoes grown in the field, but rather considers exogenous variables…”
Section: Datasetsmentioning
confidence: 99%
“…The collected data are summarized in Table 1. Jędrszczyk et al [18] and Greco et al [19] mentioned the rainfall item as one of the exogenous variables, but since this study does not consider a model that predicts the yield of tomatoes grown in the field, but rather considers exogenous variables that affect tomato yield in a facility, it is considered that there is no need to consider rainfall in particular, and it was excluded from consideration. Instead, this study found that humidity rather than rainfall affects yield in facility cultivation, so the experiment was conducted considering the maximum, minimum, and average humidity for day/night humidity.…”
Section: Datasetsmentioning
confidence: 99%
“…The distribution of precipitation and air temperatures during the growing season has a significant impact on crop yields [1][2][3]. High temperatures adversely affect plant production, resulting in shorter growing periods and shorter biomass accumulation periods [4][5][6].…”
Section: Introductionmentioning
confidence: 99%